Host plant and the predator Podisus nigrispinus: when the defense compounds of the plant affect the third trophic level. Issue 4 (18th March 2019) - Holtz, Anderson Mathias; Marinho‐Prado, Jeanne Scardini; Pallini, Angelo; Pires, André Assis; Cofler, Tatiane Pereira; Rocha, Claudiane Martins; Pazianotto, Ricardo Antônio Almeida
Abstract: Many herbivorous insects can overcome chemical plant defenses, using the plant's defensive products for their own good, as a defense against predators. Eucalyptus spp. (Myrtaceae), recently introduced in Brazil, are rich in secondary compounds; however, there are reports that these plants have been suffering from population outbreaks of defoliating Lepidoptera in Brazil. The predator Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) has been used against herbivorous insects in eucalyptus plantations, but little is known about its establishment in the field. This study aims to investigate whether the effectiveness of this predator may be affected indirectly by compounds of eucalyptus plants, when compared to guava, Psidium guajava L., a Brazilian native species of Myrtaceae. Thus, we evaluated the performance of P. nigrispinus on larvae of Thyrinteina arnobia (Stoll) (Lepidoptera: Geometridae) reared on eucalyptus (exotic species) or guava plants (native species). Podisus nigrispinus performance (reproduction and survival) was better on larvae fed on guava than on larvae fed on eucalyptus. It is possible that the negative effect on the predator's development occurred because of the plants' secondary compounds appropriated by caterpillars, due to the short coevolutionary history between eucalyptus and the predator. The data suggest that the chemical compounds that could help the plant's defenses against herbivores may also affect their natural enemies, especially when the interaction between plant and natural enemy involves an exotic plant recently introduced into the insect's habitat. Abstract : We evaluated the performance of the predator Podisus nigrispinus (Hemiptera: Pentatomidae) on caterpillars of Thyrinteina arnobia (Lepidoptera: Geometridae) fed on exotic eucalyptus or on native guava (both Myrtaceae). Reproduction and survival of the bugs were better on caterpillars from guava than on caterpillars from eucalyptus. This indicates that the predator is not well adapted to the secondary compounds of the exotic plant, possibly due to the short coevolutionary history of eucalyptus and the predator.